529 DIAGNOSIS AND TREATMENT OF HEPATOSPLENIC POST-TRANSPLANT LYMPHOPROLIFERATIVE DISORDER IN A RENAL TRANSPLANT RECIPIENT. (1st January 2006) - Criscuoli, M.; Correa, A.; Singh, G.; Genyk, Y.; Jabbour, N.; Sher, L.; Selby, R.; Mateo, R.
Abstract : Post-transplant lymphoproliferative disorder (PTLD) encompasses a wide range of hematological abnormalities occurring as a consequence of prolonged immunosuppression following solid organ transplant, with an incidence between 1 and 3% in renal transplant recipients. The development of PTLD has been linked to several risk factors, which include the type of organ transplanted, EBV and CMV serostatus of the donor and recipient prior to transplant, and the type of immunosuppressive therapies employed. In order to examine an atypical presentation for PTLD, we present a case report of a 29-year-old African American male, who received a cadaveric kidney transplant for end-stage renal disease secondary to hypertensive nephropathy. Eight months post-transplant he presented with a 2-day history of lower abdominal pain and high fever. Lab tests revealed elevated liver enzymes, and abdominal CT scan showed multiple diffuse lesions on both the liver and spleen. A subsequent biopsy was diagnostic for a diffuse large B cell lymphoma that was successfully treated with combination therapy, including reduced immunosuppression, rituximab, and antiviral medications. In a systematic review of the literature, we explore the challenges to diagnosing and characterizing cases of PTLD for the purpose of selecting appropriate treatment strategies. Many factors, including the presence of EBV or CMV viremia, degree and duration of immune suppression, time to presentation, effectiveness of antiviral prophylaxis, and type and localization of the malignancy, have significant effects on prognosis, as well as potential treatment approaches. This case highlights the importance of thorough evaluation and management of the factors that can potentiate the development and progression of PTLD in order to uniquely tailor therapy to address the needs of each patient.